A review of thermoplastic elastomeric nanocomposites for high voltage insulation applications. (8th February 2018) - Ismail, Nurul Hidayah; Mustapha, Mariatti
Abstract : Thermoplastic elastomer (TPE) has gained acceptance as third generation of polymeric materials for high voltage (HV) insulators. The interesting features showed by TPEs were found to fulfill some particular requirements for HV insulations, at least for the distribution class applications, especially at light contamination environments. Introduction of nanomaterials which widely reported to give significant improvements in the electrical, mechanical, thermal and other properties of polymer has attracted attention to the synergistic properties of combining the two complementary technologies of thermoplastic elastomers and nanocomposites. In this paper, research works on various types of TPEs having promising performance as HV insulators are thoroughly reviewed. The emergence of nanocomposites in the electrical insulation field and the important properties consideration for HV insulators as well as the processing techniques of TPE nanocomposites are also discussed. Finally, some of the past and recent developments of TPE nanocomposites focusing on the electrical insulation properties are highlighted in this article. POLYM. ENG. SCI., 58:E36–E63, 2018. © 2018 Society of Plastics Engineers